Mesenchymal Stem Cells Improve Glycometabolism and Liver Regeneration in the Treatment of Post-hepatectomy Liver Failure - Ding, Hao-ran; Wang, Jing-lin; Tang, Zhen-ting; Wang, Yue; Zhou, Guang; Liu, Yang; Ren, Hao-zhen; Shi, Xiao-lei (Frontiers in Physiology, 2019)
Background The mortality rate of post-hepatectomy liver failure (PHLF) remains very high, and liver transplantation is the only effective treatment regimen for PHLF. Cell transplantation is a potential treatment for liver diseases. Previous studies have proved that mesenchymal stem cells (MSCs) have immunomodulatory functions. In the present study, we found that MSCs promoted glycogen synthesis and liver regeneration in the treatment of PHLF. MSC transplantation also improved the survival rate of rats after 90% partial hepatectomy (PH). In our current study, we aimed to determine the efficacy and mechanism of MSC transplantation in the treatment of PHLF. Methods Mesenchymal stem cells were isolated from Sprague-Dawley rats and cultured using a standardized protocol. The MSCs were transplanted to treat acute liver failure induced by 90% PH. The therapeutic efficacy of MSCs on PHLF was verified through measuring alanine transaminase (ALT), aspartate aminotransferase (AST), international normalized ratio (INR), serum ammonia, liver weight to body weight ratio, blood glucose, and histology. To further study the mechanism of MSC transplantation in treatment for PHLF, we assessed the changes in the AKT/glycogen synthase kinase-3β (GSK-3β)/β-catenin pathway. A-674563 (AKT inhibitor) and SB216763 (GSK-3β inhibitor) were employed to validate our findings. SPSS version 19.0 was used for statistical analysis, and the independent-samples t-test was carried out to analyze the collected data. Results Mesenchymal stem cell transplantation attenuated the liver injury in acute liver failure induced by 90% PH. MSC transplantation improved the glucose metabolism and survival rate in the PHLF model. The effect of MSC transplantation on hepatocyte proliferation might be related to AKT/GSK-3β/β-catenin pathway. Conclusion Mesenchymal stem cell transplantation could be use as a potential treatment for PHLF.